Principles and problems in Philippine foreign relations - Baldoria, Pedro L.
"This is an attempt to present the principles and problems of Philippine foreign relations. The materials in this study are the result of careful selection of documents. Articles published in international magazines were added because of their pertinence in the study of Philippine foreign relations. By permission of individual authors, other articles were included, notable those of Dr. Honest A. Villanueva of the Department of History and Dr. Edward Mill of the Department of Political Science"--Preface.